On the densest packing of equal spheres into a three -dimensional convex set - Bao, Phung The; Liem, Nguyen Huy; Thanh, Ta Trung; Tuan, Vuong Anh; Tuyet, Pham Thi (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2020)
Packing problems are classic problem of mathematical optimization and are very interesting NP - hard optimization problems with a wide variety of applications. That is, no procedure is able to exactly solve them in deterministic polynomial time. In this paper, we focus on problems dealing with circular objects, being three - dimensional. A special algorithm based on the optical - geometric approach for solving the problem is suggested. We also present illustrative numerical results using our algorithm both in three - dimensional Euclidean and non - Euclidean spaces.